2017
DOI: 10.1007/s00453-017-0314-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Makespan of the Two-Valued Restricted Assignment Problem

Abstract: We consider a special case of the scheduling problem on unrelated machines, namely the Restricted Assignment Problem with two different processing times. We show that the configuration LP has an integrality gap of at most 5 3 ≈ 1.667 for this problem. This allows us to estimate the optimal makespan within a factor of 5 3 , improving upon the previously best known estimation algorithm with ratio 11 6 ≈ 1.833 due to Chakrabarty, Khanna, and Li [2].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…On better bounds. The largest gap we have witnessed in an instance is 9/6 (given in [7]). The bound on the integrality gap that was proven in this paper, 11/6, is not necessarily tight.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…On better bounds. The largest gap we have witnessed in an instance is 9/6 (given in [7]). The bound on the integrality gap that was proven in this paper, 11/6, is not necessarily tight.…”
Section: Resultsmentioning
confidence: 93%
“…In the restricted variant, however, no instance is known to have an integrality gap higher than 1.5. An instance with integrality gap 1.5 is given in [7].…”
Section: The Configuration-lpmentioning
confidence: 99%
See 1 more Smart Citation
“…Later Annamalai surpassed this with a (17/9 + ǫ)-approximation for every ǫ > 0 [1]. For this special case it was also shown that the integrality gap is at most 5/3 [6].…”
Section: Introductionmentioning
confidence: 92%
“…In [10], [7], and [6] the critical idea is to design a local search algorithm, which is then shown to produce good solutions. However, the algorithm has a potentially high running time; so it was only used to prove the existence of such a solution.…”
Section: Introductionmentioning
confidence: 99%